Culture media influences Candida parapsilosis growth, susceptibility, and virulence - Arévalo-Jaimes, Betsy V.; Admella, Joana; Blanco-Cabra, Núria; Torrents, Eduard (Frontiers in Cellular and Infection Microbiology, 2023)
Introduction Candida parapsilosis, a pathogenic yeast associated with systemic infections, exhibits metabolic adaptability in response to nutrient availability. Methods We investigated the impact of RPMI glucose supplemented (RPMId), TSB, BHI and YPD media on C. parapsilosis growth, morphology, susceptibility (caspofungin and amphotericin B), and in vivo virulence (Galleria mellonella) in planktonic and biofilm states. Results High-glucose media favors growth but hinders metabolic activity and filamentation. Media promoting carbohydrate production reduces biofilm susceptibility. Virulence differences between planktonic cells and biofilm suspensions from the same media shows that biofilm-related factors influence infection outcome depending on nutrient availability. Pseudohyphal growth occurred in biofilms under low oxygen and shear stress, but its presence is not exclusively correlated with virulence. Discussion This study provides valuable insights into the intricate interplay between nutrient availability and C. parapsilosis pathogenicity. It emphasizes the importance of considering pathogen behavior in diverse conditions when designing research protocols and therapeutic strategies.